2011
DOI: 10.1261/rna.2633611
|View full text |Cite
|
Sign up to set email alerts
|

Binding and cleavage of unstructured RNA by nuclear RNase P

Abstract: Ribonuclease P (RNase P) is an essential endoribonuclease for which the best-characterized function is processing the 59 leader of pre-tRNAs. Compared to bacterial RNase P, which contains a single small protein subunit and a large catalytic RNA subunit, eukaryotic nuclear RNase P is more complex, containing nine proteins and an RNA subunit in Saccharomyces cerevisiae. Consistent with this, nuclear RNase P has been shown to possess unique RNA binding capabilities. To understand the unique molecular recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“…Based on our data (Fig. 3) several RNase P proteins are positioned to interact with substrates: Pop1, Pop4, Pop5, and, potentially, Rpp1, consistent with recent results of enzyme-substrate crosslinking studies (Marvin et al 2011b). …”
Section: D Mapping Of Rna-protein Interactions In Yeast Rnase Psupporting
confidence: 91%
“…Based on our data (Fig. 3) several RNase P proteins are positioned to interact with substrates: Pop1, Pop4, Pop5, and, potentially, Rpp1, consistent with recent results of enzyme-substrate crosslinking studies (Marvin et al 2011b). …”
Section: D Mapping Of Rna-protein Interactions In Yeast Rnase Psupporting
confidence: 91%
“…Confirming that these RNAs are RNase P substrates in vivo is difficult given that in vitro studies (Chamberlain et al 1996;Coughlin et al 2008;Marvin et al 2011) have shown that nuclear RNase P can bind and cleave singlestranded RNA at multiple positions without clear sequence or structural requirements. Our in vitro study of cleavage preferences deliberately chose both sense and antisense RNAs across a region where the balance was affected by RNase P mutations, showing that RNase P could bind all segments across the region and cleave RNAs from both strands at multiple places (Camblong et al 2007;Coughlin et al 2008;Marvin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Like its bacterial counterpart, in addition to pre-tRNA, other possible substrates have been identified in eukaryotes (Chamberlain et al 1996;Yang and Altman 2007;Coughlin et al 2008;Wilusz et al 2008). In addition, purified nuclear RNase P's affinity for single-stranded RNA and its ability to cleave at multiple sites in vitro without obvious sequence specificity (see Marvin et al 2011) indicate a broad capacity to serve as a relatively nonspecific RNA endonuclease.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(U) 50 RNA was purchased from Integrated DNA Technology. The smaller sizes of poly(U) RNA were generated by alkaline hydrolysis and subsequent purification by passive elution from denaturing polyacrylamide gels (Marvin et al 2011). …”
Section: Rna Preparationmentioning
confidence: 99%